Assessing the implementation of user-centred design standards on assistive technology for persons with visual impairments: a systematic review - Ortiz-Escobar, Luisa Maria; Chavarria, Mario Andres; Schönenberger, Klaus; Hurst, Samia; Stein, Michael Ashley; Mugeere, Anthony; Rivas Velarde, Minerva (Frontiers in Rehabilitation Sciences, 2023)
Despite scientific and technological advances in the field of assistive technology (AT) for people with visual impairment (VI), technological designs are frequently based on a poor understanding of the physical and social context of use, resulting in devices that are less than optimal for their intended beneficiaries. To resolve this situation, user-centred approaches in the development process of AT have been widely adopted in recent years. However, there is a lack of systematization on the application of this approach. This systematic review registered in PROSPERO (CRD42022307466), assesses the application of the ISO 9241-210 human-centred design principles in allegedly “user-centred designed” AT developments for persons with VI (see Supplementary PROSPERO Protocol). The results point to a wide variation of the depth of understanding of user needs, a poor characterization of the application of the User Centred Design (UCD) approach in the initial design phases or in the early prototyping, and a vague description of user feedback and device iteration. Among the principles set out in ISO 9241-210, the application of 5.6: “the design team includes multidisciplinary skills and perspectives” is the one for which the least evidence is found. The results show there is not enough evidence to fully assess the impact of UCD in (1) promoting innovation regarding AT products and practices, and (2) Judging if AT produced following such standards is leading to better user access, wellbeing outcomes and satisfaction. To address this gap it is necessary to, first, generate better implementation of UCD in AT development and second, to strengthen evidence regarding the implementation and outcomes of using UCD for AT. To better engage with the realities of persons with VI, we propose capacity building across development teams regarding UCD, its principles and components; better planning for UCD implementation; and cross-fertilization across engineering disciplines and social and clinical science. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=307466 PROSPERO (CRD42022307466).